PEMBENTUKAN KARAKTER SISWA MELALAUI PEMBELAJARAN BOLA VOLI - Asyfa Nurul Rahma; Rekha Ratri Julianti; Abdul Salam Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is a quantitative study. The purpose of this research is to determine the impact of volleyball learning on the character formation of students and to ascertain the effectiveness of character formation through volleyball learning. This study employs an experimental method. The research was conducted at SMA Negeri 1 TelukJambe. The population of this research consists of the tenth-grade students of SMA Negeri 1 TelukJambe, totaling 358 students. The sample used in this study is Simple Random Sampling, comprising 5 individuals per class. The research design used is a one-group pretest-posttest design. The research instrument utilized a questionnaire on the character formation of students. The results of this research show significant outcomes in the average results before and after the treatment.The average pretest score was 173.80 and the average posttest score was 182.78, indicating a significant increase. Meanwhile, the results of the hypothesis testing using the paired sample T-test with data obtained from the study showed a significance value(2-tailed) of 0.000 < 0.05, meaning there is a significant effect between the average scores before and after the treatment. It can be concluded that volleyball learning can influence the character formation of 10th-grade students at SMA Negeri 1 TelukJambe.